Beyond 'desirable' values: Expanding relational values research to reflect the diversity of human-nature relationships - Hoelle, Jeffrey; Gould, Rachelle K.; Tauro, Alejandra (My University, 2023)
In recent years, environmental values have become increasingly important for understanding human-environment relationships and transitions towards sustainability. Pluralistic valuation seeks to account for values associated with the diversity of human-nature relationships. Relational values (RV) have been proposed as a concept that can aid in plural valuation. RV concern the relationships that people have with their environments. Most RV studies focus on 'desirable' or 'beneficial' RV that contribute to pro-environmental actions and sustainable outcomes. We argue that RV could be expanded to understand values that may be less environmentally beneficial. We focus our analysis on RV that exist in 'simplified' landscapes. Drawing on our research on cattle-based livelihoods in Latin America, we highlight potential approaches to the study of RV in such simplified landscapes. We then build on the examples to examine themes and principles of RV with the aim of stimulating discussion about how the concept might be refined and expanded to study a broader range of human-environment relationships. Overall, our aim is to contribute to plural valuation and offer preliminary suggestions for how RV might expand to capture the complexity of values, from those that are desirable to those which contribute to environmental degradation. Expanding the scope of RV research and the depth of the RV concept can help to understand the challenges to sustainability and contribute to the shared goals of sustainability that motivate values research. Read the free Plain Language Summary for this article on the Journal blog.
Keywords: ecosystem services; environmental change; environmental degradation; environmental valuation; human-nature connection; landscape simplification; sustainability; plural valuation